2015
DOI: 10.1590/s1516-8913201500062
|View full text |Cite
|
Sign up to set email alerts
|

Comparative evaluation of anthelmintic and antibacterial activities in leaves and fruits of Garcinia cambogia (Gaertn.) desr. and Garcinia indica (Dupetit-Thouars) choisy

Abstract: This study aimed to evaluate the in vitro anthelmintic activity and antibacterial activity of the extracts from the leaves and fruits of Garcinia indica (Dupetit-Thouars) Choisy and

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 27 publications
(22 reference statements)
0
7
0
Order By: Relevance
“…Garcinia zeylanica extracts from other species have been reported to contain hydroxy citric acid, xanthones, flavonoids and benzophenone derivatives such as garcinol [38]. Previous reports have investigated the antimicrobial activity of Garcinia Cambogia [39], and Garcinia indica [40].…”
Section: Resultsmentioning
confidence: 99%
“…Garcinia zeylanica extracts from other species have been reported to contain hydroxy citric acid, xanthones, flavonoids and benzophenone derivatives such as garcinol [38]. Previous reports have investigated the antimicrobial activity of Garcinia Cambogia [39], and Garcinia indica [40].…”
Section: Resultsmentioning
confidence: 99%
“…At a dose of 500 mg/mL of kokam extract exhibited the highest inhibition against S. aureus, and P. aeruginosa At a dose of 1000 mg/mL of kokam extract exhibited the highest inhibition against S. aureus , and P. aeruginosa . It is reported that the methanol extract of kokam cannot exert any inhibition against E. coli [ 930 ]…”
Section: Health Benefit Potentialmentioning
confidence: 99%
“…The garcinol was shown to have antibacterial activity against Bascillus sp., S. aureus, and Listeria monocytogens. Furthermore, garcinol has a significant antimicrobial effect over Helicobacter pylori, a bacterium causing gastric ulcers in the stomach [44,[62][63][64].…”
Section: Antimicrobial Activitymentioning
confidence: 99%